The Kinetics of SCID-hu Reconstitution: A Comparison between Human Splenocytes and Peripheral Blood Leucocytes - Stephen M. Thirdborough; Julie C. Chamberlain; Sue M. Swift; Roger F. L. James; Nicholas J. M. London (Cell Transplantation, 1993)
Although preliminary studies have shown that the severely combined immunodeficient (SCID)-hu mouse can reject allo tissue, they have also highlighted the current limitations of the SCID-hu model. These limitations are the need for unambiguous identification of human cells in the SCID mouse and the variability of the reconstitution efficiency. The purpose of this study was to follow the kinetics of SCID-hu reconstitution, comparing human splenocytes (SC) with peripheral blood leucocytes (PBL) to ascertain whether the presence of post-thymic progenitor cells in SC improved the efficiency of reconstitution. SCID mice were injected intraperitoneally with 5 × 107 PBL from five normal volunteers, and with 5 × 107 SC from 5 organ donor spleens. Two animals per donor were culled on weeks 2, 4, 8, and 16, and the frequency and level of SCID-hu reconstitution assessed by flow cytometric analysis of peritoneal cells and splenic leucocytes. Total serum immunoglobulin levels were measured fortnightly to follow the kinetics of B lymphocyte reconstitution. A marked degree of variability was seen in the frequency and extent of reconstitution, regardless of the source of lymphocytes. However, in comparison with PBL, human SC, predominantly T cells, were able to persist and increase in number, migrating from the peritoneal cavity to secondary lymphoid tissue. We conclude that human SC provide a better source of human lymphoid cells for SCID reconstitution than PBL.